2012
DOI: 10.1371/journal.pone.0047919
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoke Promotes Drug Resistance and Expansion of Cancer Stem Cell-Like Side Population

Abstract: It is well known that many patients continue to smoke cigarettes after being diagnosed with cancer. Although smoking cessation has typically been presumed to possess little therapeutic value for cancer, a growing body of evidence suggests that continued smoking is associated with reduced efficacy of treatment and a higher incidence of recurrence. We therefore investigated the effect of cigarette smoke condensate (CSC) on drug resistance in the lung cancer and head and neck cancer cell lines A549 and UMSCC-10B,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…Recent studies reported that various cancer cells acquired chemoresistance toward anticancer drugs by cigarette smoke condensate (CSC) or nicotine. An and colleagues reported that Akt activated by CSC induced doxurbicin resistance in lung cancer cells (39). Furthermore, in lung cancer, it was reported that nicotine induced antiapoptotic effects and cellular proliferative effects through the PI3K/Akt pathway (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported that various cancer cells acquired chemoresistance toward anticancer drugs by cigarette smoke condensate (CSC) or nicotine. An and colleagues reported that Akt activated by CSC induced doxurbicin resistance in lung cancer cells (39). Furthermore, in lung cancer, it was reported that nicotine induced antiapoptotic effects and cellular proliferative effects through the PI3K/Akt pathway (16,18).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expression of TWIST1 modulated by STAT3 enriched SP in MCF-7 cells. Drug- or chemo-resistance is also positively correlated with nicotine or cigarette smoke in many cancers [5, 10, 5961]. For example, nicotine-induced chemo-resistance in non-small cell lung cancer (NSCLC) occurs through up-regulation of XIAP and surviving [5].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, tumor hypoxia has been acknowledged to affect the responses to both radiotherapy (38) and chemotherapy (39), and has been associated with poorer OS in HNSCC (40). In addition, basic research has demonstrated that cigarette smoke condensate promotes chemoresistance via Akt-mediated regulation of the activity of the ATP-binding cassette transporter G2, and may also contribute to tumor recurrence, invasion, or metastasis by increasing the proportion of cancer stem-like cells (41). Thus, the presence of residual smoke condensate in former and current smokers may reduce the effect of chemotherapy and promote tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a recent study (42) found that 13% of cancer patients who did not smoke in the 7 days before surgery had resumed smoking within 12 months after surgery; their resumption of smoking was related to a higher perceived difficulty of quitting and lower perceptions of their cancer-related risk. Research has shown that continued smoking after diagnosis has immediate adverse impacts, including reduced efficacy of cancer treatment (5,41), increased proportions of cancer stem-like cells (41), higher rates of treatment complications and side effects (43,44), higher treatment-related weight loss (45), and a poorer quality of life (46). Unfortunately, we did not collect data on the patients who resumed or continued smoking during treatment or follow-up in this study; therefore, the possibility that some former smokers resumed smoking during treatment or follow-up cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%